Synthesis, Characterization and Preliminary Antifungal Activity of Some Co(II) and Zn(II) Complexes Derived from Oximes of 2-Acetyl Aromatic Heterocycles - Deepankar Sharma; Purnima Nag (Orbital: The Electronic Journal of Chemistry, 2021)
Present work focuses on syntheses, characterization, preliminary antifungal screening of some transition metal complexes derived from oximes of 2-acetylpyridine, 2-acetylthiophene and 2-acetylfuran; using Zn(II) and Co(II) chlorides. These newly synthesized complexes have been analyzed, characterized and compared with parent ligands on the basis of spectral techniques such as 1H-NMR, 13C-NMR IR and elemental analysis. The antifungal screening performed on derived complexes proved that they show appreciable activity against Candida albicans.DOI: http://dx.doi.org/10.17807/orbital.v13i1.1600